Definition of the minimal MEN1 candidate area based on a 5-Mb integrated map of proximal 11q13 - Courseaux, A; Grosgeorge, J; Gaudray, P; Pannett, A; Forbes, SA; Williamson, C; Bassett, D; Thakker, R; Teh, B; Farnebo, F; Shepherd, J; Skogseid, B; et al. (1996)
Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant disorder with a high penetrance characterized by tumors of the parathyroid glands, the endocrine pancreas, and the anterior pituitary. The MEN1 gene, a putative tumor suppressor gene, has been mapped to a 3- to 8-cM region in chromosome 11q13 but it remains elusive as yet. We have combined the efforts and resources from four laboratories to form the European Consortium on MEN1 with the aims of establishing the genetic and the physical maps of 11q13 and of further narrowing the MEN1 region. A 5-Mb integrated map of the region was established by fluorescence in situ hybridization on both metaphase chromosomes and DNA fibers, by hybridization to DNA from somatic cell hybrids containing various parts of human chromosome 11, by long-range restriction mapping, and by characterization of YACs and cosmids. Polymorphic markers were positioned and ordered by physical mapping and genetic linkage in 86 MEN1 families with 452 affected individuals. Two critical recombinants identified in two affected cases placed the MEN1 gene in an ≃2-Mb region around PYGM, flanked by D11S1883 and D11S449.